Re‐examining Hrabanus Maurus' letter on incest and magic. - Edholm, Matthew B. (Early Medieval Europe, 2023)
This article offers a reanalysis of Hrabanus' mid‐ninth‐century text De magicis artibus. Often read and studied as a complete work, the De magicis artibus is in fact one portion of a longer text that also discusses incest and marriage practices. Furthermore, the single surviving copy of the text is deliberately attached to another work by Hrabanus, his Poenitentiale ad Otgarium. This article argues that by examining the text in its entirety, as well as its manuscript context and edition history, Hrabanus' whole work is better understood as one of pastoral care informed by the Old Testament.